Factors Driving Moslem Purchasing Decisions Towards Halal Cosmetic - Yeyen Novita (Universitas Islam Negeri (UIN) Salatiga, 2025)
This study aims to analyze the factors influencing Muslim consumers' purchasing decisions towards halal cosmetic products, focusing on a leading local brand in Indonesia, Wardah. The variables examined include green marketing, consumer ethnocentrism, halal lifestyle, and Islamic consumption ethics. The research uses a quantitative approach, with purposive sampling, involving 385 respondents from Wardah’s customer. Data analysis using IBM SPSS 27. Based on research results that consumer ethnocentrism, halal lifestyle, and Islamic consumption ethics have significant positive effect on purchasing decisions. Among these, Islamic consumption ethics is the strongest predictor, indicating that consumers highly value Islamic principles such as halal status, simplicity, and social benefit in their consumption behavior. Meanwhile, the green marketing no significant effect, which is suspected to be due to the respondents' low purchasing power, as the majority are students with limited income, making environmental aspects not yet a primary consideration in purchase decisions. This study emphasizes the importance of integrating ethical, religious, and cultural values in halal product marketing strategies. Especially in the context of Indonesia, where Muslim consumers make up a large and diverse market, understanding these driving factors is crucial for building trust and sustained loyalty in the halal cosmetics industry.